Perceptions of wellness and burnout among certified athletic trainers: sex differences - Naugle, K. E.; Behar-Horenstein, L. S.; Dodd, V. J.; Tillman, M. D.; Borsa, P. A. (Journal of Athletic Training, 2013)
Context: Athletic trainers are exposed to various stressors, increasing the potential for burnout and decreasing perceived wellness. Burnout and decreased perceived wellness can result from many factors: years of experience, hours per week worked, or decreased levels of physical activity. Another factor that accounts for a portion of the variance is sex differences. Objective: To determine the differences in burnout, physical activity, and perceived wellness scores relating to sex in District 9 of the National Athletic Trainers' Association (NATA). Design: Cross-sectional study. Setting: Web-based questionnaire. Patients or Other Participants: Athletic trainers who were included in the e-mail directory of NATA District 9 (men = 232, women = 158). Intervention(s): A 19-item questionnaire for burnout, a 36-item questionnaire for perceived wellness, and a 16-item activity questionnaire for physical activity and demographics. Main Outcome Measure(s): The variables included demographics (hours per week worked, years of experience, sex), Copenhagen Burnout Inventory (CBI; scores range from 0-100, and higher scores represent a higher level of burnout), Perceived Wellness Survey (PWS; scores range from 1-36, and scores close to 29 are considered healthy), and Baecke Physical Activity Questionnaire (BPAQ; scores range from 1-15, and higher scores represent more physical activity). Results: Of the 1560 members contacted, 390 responded (response rate = 25%), and 59.5% (n = 232) were male. The mean scores were 38.73 ± 16.9 for men and 46.2 ± 17.1 for women for the CBI, 16.68 ± 2.76 for men and 16.41 ± 2.81 for women for the PWS, and 8.42 ± 1.32 for men and 8.77 ± 1.36 for women for the BPAQ. Men and women worked an average of 55.60 ± 26.03 and 47.86 ± 20.57 hours per week, respectively, and had a mean experience of 14.79 ± 9.86 and 8.92 ± 6.51 years, respectively. Women reported a higher level of burnout (t388 = -4.255, P = .001) and greater levels of physical activity (t388 = -2.52, P = .01) than men. Men reported working more hours (t388 = 3.131, P = .002) and having more years of experience (t388 = 6.568, P = .001) than women. Perceived wellness was not different between sexes (t388 = 0.958, P = .34). Conclusions: Our results suggest that women experienced moderate to high burnout and men experienced moderate burnout. Interestingly, men reported lower levels of burnout but worked more hours than women. Future researchers should focus on why women experience higher levels of burnout but work fewer hours. These findings may lead to educational interventions that might reduce burnout and increase professional longevity and quality of work.